2020
DOI: 10.1007/s12187-020-09779-9
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stress and Subjective Wellbeing among Children -Evidence from Finland

Abstract: In this article we analyse how subjective wellbeing amongst Finnish children is associated with experiences of financial stress, that is, worries about money and one’s financial situation. We focus on both affective and cognitive components of subjective wellbeing in order to receive a broader understanding on children’s subjective wellbeing. We use Finnish data from the International survey of children’s lives conducted by the Children’s Worlds Project during the years 2013–2014. The results show that experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Understanding how the pandemic has affected children's everyday stress would provide us with essential information about children's current psychological well-being. Particularly, there is a need to closely examine the sub-areas of children's daily stress, including family, academic performance, peer relationships, and financial pressure [45][46][47]. It is possible that stress in some contexts is exacerbated, while in other contexts, decreases or does not change under the pandemic.…”
Section: Children's Stress and Life Satisfaction During The Covid-19 Pandemicmentioning
confidence: 99%
“…Understanding how the pandemic has affected children's everyday stress would provide us with essential information about children's current psychological well-being. Particularly, there is a need to closely examine the sub-areas of children's daily stress, including family, academic performance, peer relationships, and financial pressure [45][46][47]. It is possible that stress in some contexts is exacerbated, while in other contexts, decreases or does not change under the pandemic.…”
Section: Children's Stress and Life Satisfaction During The Covid-19 Pandemicmentioning
confidence: 99%
“…In addition, family, wealth, and the possibility of choice are key factors in subjective well-being which is closely related to self-esteem. Therefore, adolescents without financial support are at risk of low self-esteem [ 39 ]. COVID-19 caused an economic crisis, and 42.3% of adolescents expressed decreased confidence in society 42.3% [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in line with studies among adults (Diener et al, 2018), socioeconomic resources consistently show stronger associations with cognitive well-being component (life satisfaction) than with affective ones. Lindberg et al (2021) found that affective well-being components correlate stronger with individual personal characteristics, such as self-confidence and health, whilst cognitive well-being components correlate stronger with external variables, such as family and societal dimensions. Furthermore, the literature shows that researchers often claim to investigate well-being, while using only life satisfaction measures in their studies, which is not aligned with the existing findings that posit positive and negative affect as the main components of the children's well-being construct (Savahl et al, 2021;Tomyn & Cummins, 2011).…”
Section: Hedonic Approach To Well-beingmentioning
confidence: 92%